Phytochemical and Biological Investigation of Bridelia tomentosa Blume Growing in Bangladesh - Anjum, Adeeba; Kuddus, Md Ruhul; Sultan, Md Zakir; Mansur, Abdullah Al; Hasan, Choudhury M; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Bridelia tomentosa Blume is a small evergreen tree which has enormous folklore applications in the treatment of colic, traumatic injury, epidemic influenza and neurasthenia. The main purpose of this study was to isolate bioactive compounds from the stem bark of B. tomentosa growing in Bangladesh. Extensive chromatographic separation and purification of the methanolic extract of stem bark of B. tomentosa led to the isolation of four compounds. The purified constituents were identified as friedoolean-5(6),14(15)-dien-3-one (1), β-taraxerol (2), D4- stigmasterone (3) and lupeol (4) by extensive analysis of NMR spectroscopic data. While compound 1 is appeared to be new, the other compounds (2-4) have been isolated for the first time from this plant. β-taraxerol (2) demonstrated significant cytotoxic activity against the brine shrimp Artemia salina and moderate to strong antimicrobial efficacy with the highest inhibitory potential against Salmonella Typhi (zone of inhibition = 21.3 mm) and Sarcina lutea (zone of inhibition =20.8 mm). In conclusion, B. tomentosa has been found to be a rich source of secondary metabolites and thus it may be studied further in order to isolate of more bioactive constituents. Dhaka Univ. J. Pharm. Sci. 20(2): 213-218, 2021 (December)